Menopause and lipid profile: a comparative observational study - Banstola, Hemanta; Shrestha, Tirtha man; Maharjan, Ramesh Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Hormonal changes after menopause such as low plasma estrogen levels and elevated Luteinizing Hormone and Follicle Stimulating Hormone levels had a significant effect on plasma lipid metabolism. The incidence of atherosclerotic diseases is more in postmenopausal women compared to premenopausal women. The objective of this study was to find out the effect of menopause on lipid profile among apparently healthy postmenopausal women. Method: This was an unmatched comparative observational study carried out among apparently healthy pre and postmenopausal women aged between 35-65 years presented at the General Health Check-up OPD of Tribhuvan University Teaching Hospital, Nepal from May 2019 to June 2020.The sample size was 128 in each group and data were analyzed using an independent t-test to compare the mean between the two groups and were considered significant when the p-value is less than 0.05. Result: Among 128 postmenopausal women, mean total cholesterol 191.59±35.78 mg/dl, triglyceride 143.44±72.39 mg/dl, HDL-cholesterol 45.01±9.99 mg/dl, LDL-cholesterol116.43±31.79 mg/dl and VLDL cholesterol was found to 28.69±14.48 mg/dl. Similarly, among 128 premenopausal women, mean TC 164±35.03 mg/dl, TGs 125.52±65.84mg/dl, HDL cholesterol 41.66±7.66 mg/dl, LDL-cholesterol96.95 ±31.78 mg/dl and VLDL-cholesterol was found to 25.10 ± 13.17 mg/dl. Mean TC, TGs, LDL-cholesterol, and VLDL-cholesterol along with cardiac risk ratio (TC/HDL and LDL/HDL) were found to be statistically significantly higher in postmenopausal women compared to premenopausal women. We also observed significantly higher HDL cholesterol in the postmenopausal group. Conclusion: Menopause leads to an increase in mean TC, TGs, LDL-cholesterol, and VLDL-cholesterol along with an increased cardiac risk ratio among postmenopausal women compared to premenopausal women.